Volume 4: Heat Transfer; Electric Power; Industrial and Cogeneration 1994
DOI: 10.1115/94-gt-180
|View full text |Cite
|
Sign up to set email alerts
|

The Coefficient of Discharge of 30° Inclined Film Cooling Holes With Rounded Entries or Exits

Abstract: The coefficients of discharge of 30° inclined holes having a length to diameter ratio of 6, and rounded entries or exits have been measured for a range of crossflow conditions. The rounding radius varied from 0 to 1 hole diameters, and the crossflow Mach numbers from 0 to 0.5. Rounding the hole inlet was found to be beneficial, with increases of up to 15% being obtained at high coolant (inlet) side crossflow Mach numbers. Rounding the exit produced no significant benefit. The cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…It is well known that, for sharp edged holes, losses within the hole are dominated by inlet separation for small lid ratios, but that frictional losses increase steadily with increasing lid ratio (Andrews and Mkpadi, 1983). The values without crossflow closely agree with those predicted by Lichtarowicz et al (1965), who concluded that for lid ratios in the range 2-10, the Cd for choked flow would be given by :…”
Section: Measurements With External Crossflowsupporting
confidence: 77%
See 2 more Smart Citations
“…It is well known that, for sharp edged holes, losses within the hole are dominated by inlet separation for small lid ratios, but that frictional losses increase steadily with increasing lid ratio (Andrews and Mkpadi, 1983). The values without crossflow closely agree with those predicted by Lichtarowicz et al (1965), who concluded that for lid ratios in the range 2-10, the Cd for choked flow would be given by :…”
Section: Measurements With External Crossflowsupporting
confidence: 77%
“…that commonly highlighted in the literature), in that the discharge coefficient with crossfiow is lower than the non-crossflow case for all pressure ratios. The data shows good agreement with an extrapolated version of sharp-edged hole data given by Hay et al (1994a;Ild = 6.0,9 = 30°, a In contrast, the data presented in Figure 8 (Row 3; lid = 7.5, e = 28 0 and a = 7°) illustrates the case where, at the same pressure ratio, the with-crossflow data is initially lower than the noncrossflow data, but becomes higher than the non-crossflow case as the pressure ratio increases, and then tends to the same value at the critical pressure ratio (PR = 1.89), where the flow chokes. This is termed the 'crossover' phenomenon by the authors.…”
Section: Measurements With External Crossflowsupporting
confidence: 76%
See 1 more Smart Citation
“…They concluded that inlet radiusing and chamfering increases the discharge coefficient substantially. Hay et al (1994) measured 146 M. E. TASLIM AND S. UGARTE the discharge coefficients for 30 • inclined cylindrical holes with rounded inlet and exit and a range of cross-flows on both sides of the holes. A major conclusion of this study was that while inlet radiusing was beneficial, rounding of the exit did not produce any significant benefit.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that inlet radiusing and chamfering increases the discharge coefficient substantially. Hay et al (1994) measured 146 M. E. TASLIM AND S. UGARTE the discharge coefficients for 30…”
Section: Introductionmentioning
confidence: 99%